Pengembangan Aplikasi Pusat Pelayanan Pengaduan Masyarakat (P3M) Berbasis Web Studi Kasus : Dinas Komunikasi dan Informatika Kabupaten Sidoarjo - Alfi Julisar Dwitama; Widhy Hayuhardhika Nugraha Putra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Kabupaten Sidoarjo Government has public service function, one of which is public complaints services. This public complain service is managed by an agency called the Public Complaints and Service Center (P3M) which is located at the Communication and Information Office of Sidoarjo Regency. Public complaints services can be done through several media such as through social media and the P3M application website. From the media, public complaints services can be done but have problems regarding user accessibility and interest in P3M applications. In addition, some additional features are needed for the P3M application. Based on the problem, it is necessary to develop a public complaints service application website that can solve the problem. Development is carried out by providing business process modeling, requirement analysis, designing and implementing community complaint service systems by implementing an object oriented approach. Then the system is tested to find out which systems or applications that have been developed in this study can run according to identified requirement. Application development is done by using the waterfall model method and using the Laravel php framework and testing using the validation, responsivity, and compatibility testing method. The results of the study indicate that the system can run well in accordance with expectations and is able to facilitate public complaints services.